Treasure hunters / 8. - Smith, Jeff, 1960 February 27- (Bone, 2008)
Tensions come to a head in the eighth epic volume of the BONE series. The Bone cousins, Gran'ma Ben, and Thorn finally reach the city of Atheia, where they reunite with old friends and plan to thwart The Lord of the Locusts. The Pawan army has joined forces with Briar and the rat creatures, and danger increases as Thorn's visions get stronger. Meanwhile, Phoney Bone is convinced Atheia is a city rich in gold, and he is determined to find it!